An Anglo-Saxon great hall complex at Sutton Courtenay/Drayton, Oxfordshire : a royal centre of early Wessex? - Brennan, N; Hamerow, H (Routledge, 2015)
An archaeological evaluation at the site of an Anglo-Saxon ‘great hall complex’ at Sutton Courtenay/Drayton, Oxfordshire (NGR 448733 193671), previously known primarily from aerial photographs and metal-detector finds, included the partial excavation of two large timber buildings. One of these had been cut into a prehistoric mound or bank and proved to be the largest Anglo-Saxon ‘great hall’ yet identified. The smaller building overlay an earlier sunken-featured building of probable sixth-century date. The geophysical survey and excavation provide significant new information regarding the site, which is probably that of an undocumented royal centre associated with the earliest rulers of the West Saxons.